Ekonomi Dunia dalam Tinjauan Teori Realitas Terintegrasi (IRT): Dari Akumulasi Entropi Menuju Keseimbangan Global - M. Shoim; La Himmah il Princess Choris (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The contemporary global economy faces a profound paradox: global Gross Domestic Product (GDP) growth and technological innovation are reaching all-time highs, yet inequality, climate crisis, and geopolitical instability are simultaneously worsening. This article employs Integrated Reality Theory (IRT) as an analytical framework to diagnose the systemic roots of this paradox. By mapping the global economy onto five IRT variables—Energy (E), Information (I), Entropy (S), Consciousness (C), and Evolution (v)—this article demonstrates that the world's economic architecture is experiencing a fundamental disequilibrium: exponential growth in E and I is not matched by adequate management of S. The accumulation of entropy, manifested in three dimensions—global debt, ecological degradation, and social polarization—has reached a critical point where every addition of energy and information only exacerbates systemic instability. This article offers a paradigmatic reorientation through the enhancement of C as the primary strategy for reducing S, while proposing the policy framework of Techno-Spiritual Based Developmentalism (TSBD) as a middle path between market fundamentalism and state fundamentalism. The function Φ = (E × I / S) × C is treated as a heuristic model for diagnosis, not a deterministic law. IRT opens the possibility for developing an economic model that integrates material efficiency, ecological sustainability, and ethical reflexivity into a unified systemic framework.